Automatic Control System Using Arduino UNO and Web-Based Monitoring For Watering Chili Plants - Rizal Tjut Adek; Muhammad Fikry; Helmi Naluri; Risawandi . (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2022)
Caring for chili plants in addition to fertilization is proper watering. Watering is sometimes done less regularly in this case is the timeliness other than that the temperature and soil moisture are not paid attention to by the chili plant keepers. Moreover, if the chili plant keeper has other activities, then the watering of the plants will be more irregular, making the production of chili plants not optimal and even chili plants can die. By utilizing Arduino and several supporting sensors, we can determine the right watering time. In this research, data is taken from sensors, such as soil moisture sensors, air humidity sensors, temperature sensors and ultrasonic sensors which then the data will be sent to the website to be displayed to the user. Sensors are devices used to detect changes in physical quantities such as pressure, force, electrical quantities, light, motion, humidity, temperature, speed and other environmental phenomena. The purpose of this study was to measure soil moisture, air humidity, temperature as a determinant of the right watering time for chili plants and make it easier for farmers to monitor and water chili plants. This is evidenced in the Blackbox testing method on the system design, from the test results it is known that this system has been running well and is in accordance with what is expected.